Potencial competitivo de circuito turístico: uma análise da rota dos tropeiros no Centro-Oeste de Minas Gerais - Oliveira, Jussara Maria da Silva Rodrigues (2007)
Competitive characteristics as the great territorial extension, the natural environment, the cultures and habits of each region, amongst others. To stimulate the development of the tourist sector, the Minas Gerais State government created 46 tourist circuits, distinguishing the "Rota dos Tropeiros", constituted by Arcos, Formiga, Itapecerica, Lagoa da Prata and Santo Antônio do Monte, all cities in the center-west region. By the way, the objective of this work was to evaluate the tourist potential of this route, checking if the economic organization forms can be reverted in benefit for the tourist activity. Specifically, one searched to describe the profile of the tourist, to identify tourist atractive and to measure competitiveness index of the price, environmental quality, technological advances, deve4lopment and human resources of the tourist route cities and to point the organization ways of the tourist activity different sectors. The methodology consisted, basically, in the structuralized questionnaires employed to 400 tourist, being 80 for each city. The competitiveness index neasure was made using a derivation from World Travel and Tourist Council method, as described by Gooroochurn & Sugiyarto (2005). The results appointed that the profile tourists majority was a bachelor men, undergraduates, with age oscillating between 26 to 30 years old, they was born in Minas Gerais and having a month wage oscillating between 4 and 6 minimun. It was observed existence of a great amount of tourist points as Lago de Furnas, the waterfalls and grottos, the night establishments, the exposition parks, among other attractive as the religious and folklores parties as the carnival and Folia de Reis and congado parties. Others tourist points identified was PUC and Unifor undergraduate institutues, the colonial civil architecture as Sobrado Dom Dico and churches, between many ones. In relation to competitiveness mechanisms measurement, the Formiga city was most circuit competitive, followed, respectively by Arcos, Lagoa da Prata, Itapecerica and Santo Antônio do Monte. Finally, this study showed that economic activities organization way in Arcos and Santo Antônio do Monte are structuralized around calcareous rock and pyrotechnical industrial cluster; in Formiga, the existing arrangement is textile industrial incomplete cluster; in Itapecerica and Lagoa da Prata do not exist economic organization arrangements as clusters (incomplete or complete), without cooperation nets between ones. As general conclusion, it believe that region potentialities stimulation allied to employ by directed economic policies can develop the circuit competitiveness, bringing touris, resident and public organizations beneficial.